EFSUMB Guidelines on Interventional Ultrasound (INVUS), Part V – EUS-Guided Therapeutic Interventions (short version) - Fusaroli, P.; Jenssen, C.; Hocke, M.; Burmester, E.; Buscarini, E.; Havre, R. F.; Ignee, A.; Saftoiu, A.; Vilmann, P.; Nolsøe, C. P.; Nürnberg, D.; D’Onofrio, M.; Gilja, O. H.; Lorentzen, T.; Piscaglia, F.; Sidhu, P. S.; Dietrich, C. F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
The fifth section of the Guidelines on Interventional Ultrasound (INVUS) of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) assesses the evidence for all the categories of endoscopic ultrasound-guided treatment reported to date. Celiac plexus neurolysis and block, vascular intervention, drainage of fluid collections, drainage of biliary and pancreatic ducts, and experimental tumor ablation techniques are discussed. For each topic, all current evidence has been extensively analyzed and summarized into major recommendations for reader consultation (short version; the long version is published online).
Keywords: guidelines; endoscopic ultrasound; EUS guidance; pseudocyst drainage; cholangiodrainage; pancreatic duct drainage; celiac plexus neurolysis